Ummi Method for Madrasah Teacher Professionalism: Is it Effective for Improving Al-Qur'an Reading Skills? - Syahraini Tambak; Abd Rahman bin Abd Ghani; Desi Sukenti; Miftah Syarif; Surya Susanti (POTENSIA: Jurnal Kependidikan Islam, 2023)
Many research has been carried out on reading skills of the al-Qur’an, but it has not been found involving the ummi method in madrasah learning. This study aims to determine the effect of the ummi method in developing the skill to read the al-Qur’an in tsnawiyah madrasah students. Using data collected from the ummi method intervention program, this study used a quasi-experimental method to assess how the ummi method had an effect on the al-Qur'an reading skills of tsanawiyah madrasah students. The sample of this study was 182 students, of which 89 were for the experimental class and 93 students were for the control class. Data was collected using tests and analyzed using t-test. The results of this study are that the ummi method has an effect on developing students' ability to read the al-Qur’an. This is proven where there is a difference between the use of the ummi method and the conventional method in developing the ability to read the al-Qur’an for students at madrasah tsanawiyah. Thus, this research contributes to the development of the theory of the ability to read the al-Qur’an by involving the ummi method.    TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in Japanese Translate to English    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Japanese to EnglishPRO Never translate Japanese Never translate ejournal.uin-suska.ac.id